2021
DOI: 10.1007/s10120-021-01162-z
|View full text |Cite
|
Sign up to set email alerts
|

International cost-effectiveness analysis evaluating endoscopic screening for gastric cancer for populations with low and high risk

Abstract: Background Gastric cancer remains one of the 3 most common causes of cancer death worldwide. Understanding the health and economic factors that affect screening cost-effectiveness in different countries will help address when and where it makes most sense to screen for gastric cancer. Methods We performed a cost-effectiveness analysis using a Markov model to compare screening and surveillance strategies for gastric cancer in Brazil, France, Japan, Nigeria, and the United States. Primary outcome was the increme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Gastric cancer is the 4th most prevalent malignant tumor. Due to the lack of early diagnostic markers, patients are commonly diagnosed at terminal stages, with tumors that have metastasized to proximal or even remote regions in the body ( Lin et al, 2019 ; Arnold et al, 2020 ; Ascherman et al, 2021 ; Puliga et al, 2021 ). Su et al (2019) discovered that LINC01116 and CASC11 were upregulated in GC tissues, compared with cancer-adjacent tissues, and were positively correlated with clinical stages.…”
Section: Expression and Clinical Characteristics Of Linc01116 In Various Cancer Typesmentioning
confidence: 99%
“…Gastric cancer is the 4th most prevalent malignant tumor. Due to the lack of early diagnostic markers, patients are commonly diagnosed at terminal stages, with tumors that have metastasized to proximal or even remote regions in the body ( Lin et al, 2019 ; Arnold et al, 2020 ; Ascherman et al, 2021 ; Puliga et al, 2021 ). Su et al (2019) discovered that LINC01116 and CASC11 were upregulated in GC tissues, compared with cancer-adjacent tissues, and were positively correlated with clinical stages.…”
Section: Expression and Clinical Characteristics Of Linc01116 In Various Cancer Typesmentioning
confidence: 99%
“…Screening of high-risk populations has been proved to increase the diag diagnosis of early-gastric cancer and to improve long-term survival [13,14]. However, in European countries, there is no designated screening program for gastric cancer [15,16]. Therefore, diagnosing early gastric cancer, in the asymptomatic period, is the exception and not the rule [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Our study also showed that biennial endoscopic screening is not cost-effective for asymptomatic Japanese population aged 50 years. Ascherman et al showed that biennial endoscopic screening is not cost-effective, while 5-year and 10-year endoscopic screening is cost-effective compared to no screening in the general Japanese population aged 40 years through 35 successive 1-year cycles of the model until age 75 [ 41 ]. Our study also demonstrated that endoscopic screening at the 1-year, 2-year, and 3-year intervals is not cost-effective in the Japanese population aged 40 years.…”
Section: Discussionmentioning
confidence: 99%